English SWOT Analysis In Strategic Management Process: University Hospital Example (Third Sector Social Economic Review, 2025)
The aim of this study is to emphasize the importance of the strategic management process, to apply SWOT analysis on the example of a university hospital, to evaluate the factors in the internal and external environment of the hospital, and to help determine strategic goals. In the study, criteria including the strengths and weaknesses of hospitals, opportunities and threats in the internal/external environment were determined for SWOT analysis. With the AHP questionnaire, data were collected and analyzed from three foundation university hospital managers of a health group. The study provides a broad perspective of the factors affecting the strategic management process in hospitals. A total of 28 main criteria and 99 sub-criteria were identified in the study. Among these sub-criteria, the list of the top five items, due to their high weights, is as follows, according to the SWOT matrix:"Health service in our country is economical for health tourists (O)", "There is fluctuation in the exchange rate (T)" and "There is a change in plans due to the constantly changing exchange rate (T)", Qualified health personnel want to live in Istanbul (O)", "Medical devices and technological infrastructure are good (S)", "Personnel who gain experience go to other hospitals" (W). This study shows that SWOT analysis is an appropriate tool in the strategic management process for university hospitals and can be used to increase and maintain the hospital's competitive advantage. The results of the study aim to contribute to a better understanding and implementation of the strategic management process by hospital managers and policy makers.
Keywords: Strategic Management; Strategy; SWOT Analysis; AHP; Hospital